Progranulin causes adipose insulin resistance via increased autophagy resulting from activated oxidative stress and endoplasmic reticulum stress. Issue 1 (December 2017) - Guo, Qinyue; Xu, Lin; Li, Huixia; Sun, Hongzhi; Liu, Jiali; Wu, Shufang; Zhou, Bo
Abstract Background Progranulin (PGRN) has recently emerged as an important regulator for insulin resistance. However, the direct effect of progranulin in adipose insulin resistance associated with the autophagy mechanism is not fully understood. Methods In the present study, progranulin was administered to 3T3-L1 adipocytes and C57BL/6 J mice with/without specific inhibitors of oxidative stress and endoplasmic reticulum stress, and metabolic parameters, oxidative stress, endoplasmic reticulum stress and autophagy markers were assessed. Results Progranulin treatment increased iNOS expression, NO synthesis and ROS generation, and elevated protein expressions of CHOP, GRP78 and the phosphorylation of PERK, and caused a significant increase in Atg7 and LC3-II protein expression and a decreased p62 expression, and decreased insulin-stimulated tyrosine phosphorylation of IRS-1 and glucose uptake, demonstrating that progranulin activated oxidative stress and ER stress, elevated autophagy and induced insulin insensitivity in adipocytes and adipose tissue of mice. Interestingly, inhibition of iNOS and ER stress both reversed progranulin-induced stress response and increased autophagy, protecting against insulin resistance in adipocytes. Furthermore, the administration of the ER stress inhibitor 4-phenyl butyric acid reversed the negative effect of progranulinin vivo . Conclusion Our findings showed the clinical potential of the novel adipokine progranulin in the regulation of insulin resistance, suggesting that progranulin might mediate adipose insulin resistance, at least in part, by inducing autophagy via activated oxidative stress and ER stress.